An investigation into reinforced and functionally graded lattice structures. (March 2017) - Maskery, Ian; Hussey, Alexandra; Panesar, Ajit; Aremu, Adedeji; Tuck, Christopher; Ashcroft, Ian; Hague, Richard
Lattice structures are regarded as excellent candidates for use in lightweight energy-absorbing applications, such as crash protection. In this paper we investigate the crushing behaviour, mechanical properties and energy absorption of lattices made by an additive manufacturing process. Two types of lattice were examined: body-centred-cubic (BCC) and a reinforced variant called BCC z . The lattices were subject to compressive loads in two orthogonal directions, allowing an assessment of their mechanical anisotropy to be made. We also examined functionally graded versions of these lattices, which featured a density gradient along one direction. The graded structures exhibited distinct crushing behaviour, with a sequential collapse of cellular layers preceding full densification. For the BCC z lattice, the graded structures were able to absorb around 114% more energy per unit volume than their non-graded counterparts before full densification, 1371 ± 9 kJ/m 3 versus 640 ± 10 kJ/m 3 . This highlights the strong potential for functionally graded lattices to be used in energy-absorbing applications. Finally, we determined several of the Gibson–Ashby coefficients relating the mechanical properties of lattice structures to their density; these are crucial in establishing the constitutive models required for effective lattice design. These results improve the current understanding of additively manufactured lattices and will enable the design of sophisticated, functional, lightweight components in the future.